Developing thermally stable high-entropy alloys using a phase-diagram method - Huang, Rui; Amar, Abdukadir; Jiao, Wenna; Wang, Shudao; Lu, Yiping (Materials characterization, 2025)
Refractory high-entropy alloys (RHEAs) designed using empirical formulas face challenges in maintaining structural stability and mechanical properties at intermediate temperatures after heat treatment owing to limited guidance on structural stability. This study aimed to propose an element-addition method to create thermally stable RHEAs. The alloys within the suggested composition provided by this method maintained a single solid–solution phase after prolonged annealing at 600 °C, 700 °C, 800 °C, and 1000 °C for 100 h. Further, the alloys exhibited favorable mechanical properties. For example, the tensile yield strength (σ0.2) and fracture elongation of the alloy heat-treated at 800 °C for 100 h were 830 MPa and 11 %, respectively. The peak compressive true stress of these alloys at 800 °C exceeded 480 MPa. The mechanical performance at both room and elevated temperatures was comparable to those of the most as-cast RHEAs. The study identified Mo, Nb, and Ti elements as beneficial for forming a stable single-phase structure, with Al content strictly regulated. Characterization via x-ray diffraction and electron backscatter diffraction revealed that dislocation was the primary deformation mechanism at room temperature. In contrast, grain boundary sliding and dynamic recrystallization contributed to flow stress softening of the alloy at high temperatures. Besides providing a meaningful paradigm for obtaining stable RHEAs, this study offered insights into obtaining alloys with better high-temperature properties, which are essential for advancing their industrial applications. [Display omitted] •An element-addition method was proposed.•The alloy retains a single-phase structure after intermediate temperatures heat treatment for 100 h.•The alloy exhibited superior mechanical properties stability.•Grain boundary sliding, dynamical recrystallization, and dislocation annihilation lead to flow stress softening.